Detection of antineutrophil cytoplasmic antibodies (ANCAs): a multicentre European Vasculitis Study Group (EUVAS) evaluation of the value of indirect immunofluorescence (IIF) versus antigen-specific immunoassays. Issue 4 (1st August 2016) - Damoiseaux, Jan; Csernok, Elena; Rasmussen, Niels; Moosig, Frank; van Paassen, Pieter; Baslund, Bo; Vermeersch, Pieter; Blockmans, Daniel; Cohen Tervaert, Jan-Willem; Bossuyt, Xavier
Abstract : Objective: This multicentre study was performed to evaluate the diagnostic accuracy of a wide spectrum of novel technologies nowadays available for detection of myeloperoxidase (MPO) and proteinase 3 (PR3)-antineutrophil cytoplasmic antibodies (ANCAs). Methods: Sera (obtained at the time of diagnosis) from 251 patients with ANCA-associated vasculitis (AAV), including granulomatosis with polyangiitis and microscopic polyangiitis, and from 924 disease controls were tested for the presence of cytoplasmic pattern/perinuclear pattern and atypical ANCA (A-ANCA) by indirect immunofluorescence (IIF) (at two sites) and for the presence of PR3-ANCA and MPO-ANCA by eight different immunoassays. Results: The area under the curve (AUC) of the receiver operating characteristic curve to discriminate AAV from controls was 0.923 (95% CI 0.902 to 0.944) and 0.843 (95% CI 0.814 to 0.871) for the two IIF methods. For the antigen-specific immunoassays, the AUC varied between 0.936 (95% CI 0.912 to 0.960) and 0.959 (95% CI 0.941 to 0.976), except for one immunoassay for which the AUC was 0.919 (95% CI 0.892 to 0.945). Conclusions: Our comparison of various ANCA detection methods showed (i) large variability between the two IIF methods tested and (ii) a high diagnostic performance of PR3-ANCA and MPO-ANCA by immunoassay to discriminate AAV from disease controls. Consequently, dual IIF/antigen-specific immunoassay testing of each sample is not necessary for maximal diagnostic accuracy. These results indicate that the current international consensus on ANCA testing for AAV needs revision.